Students’ Vocabularies Learning through Scrabble Games - Nurwayuni, Rika (Universitas Pendidikan Ganesha, 2023)
Problem in learning and teaching English still exist in school. Vocabulary is not a developmental skill or one that can ever be seen as fully mastered. The objective of the research was to analyze students’ vocabularie through scrabble games. This was a classroom action research conducted in 2 cycles, where each cycle consisted of five meetings. The instrument of collecting the data was observation sheet, interview, test and documentation. The data was obtained with quantitative analysis to calculate the percentage of completeness. Based on the analysis of the data it turned out that the students’ vocabularies had increased in each cycle. From the results of data analysis it showed an increase on students’ scores from pre-test to post-test I and post-test II. That was proven by data; students’ scores in the post-test I, the lowest score was 65 and the highest score was 80; Students' scores in post test II, the lowest score was 66 and the highest score was 85. In the pre-test, there were 8% (2 of 25 students) who scored ≥75. In post-test, there were 52% (13 out of 25 students) who scored ≥75. In post-test II, there were 84% (21 of 25 students) who scored ≥75. The conclusion of the research was 1 the learning method by using scrabble games on grade VII was more effective and more active.